Multi‐Point Observations of Modulated Whistler‐Mode Waves and Energetic Electron Precipitation. Issue 12 (24th December 2021) - Qin, Murong; Li, Wen; Ma, Qianli; Woodger, Leslie; Millan, Robyn; Shen, Xiao‐Chen; Capannolo, Luisa
Abstract: In this study, we present simultaneous multi‐point observations of whistler‐mode waves detected by RBSP‐B, associated with conjugate electron precipitation observed through enhanced BARREL X‐rays at L  ∼ 6 from noon to dusk. Both long period modulation at periods of several to tens of minutes and short period modulation at about tens of seconds are observed in X‐ray measurements. Similar periodicities are also observed for whistler‐mode wave amplitude. We show that the correlation coefficient between whistler‐mode waves and electron precipitation is high in several regions, including plumes and plasma trough. Ultra‐low‐frequency waves (8–30 mHz), which have been suggested to play a potential role in precipitating electrons by modulating whistler‐mode wave intensity or loss cone size, show a weak correlation with whistler‐mode wave amplitudes and the X‐ray counts during the conjunction. We further evaluate whistler‐mode wave driven electron precipitation using a physics‐based technique. The time evolution of the modeled electron precipitation is found to be remarkably consistent with the modulation in the BARREL X‐ray counts both in plumes and plasma trough. By taking advantage of the high‐resolution wave data and close conjunction, we provide strong evidence that whistler‐mode waves are not only directly responsible for the longer modulation (several to tens of minutes), but also the shorter modulation (tens of seconds) of the electron precipitation. Plain Language Summary: Whistler‐mode waves, which are right‐handed polarized electromagnetic plasma waves commonly observed in the Earth's inner magnetosphere, have been known to be efficient in precipitating electrons. Extensive studies have revealed the pitch angle scattering of energetic electrons caused by whistler‐mode waves in the plasmasphere (near‐Earth regions where cold and dense plasmas are corotating with the Earth) or in the plasma trough (regions further away from the Earth where cold plasmas are less dense). However, the role of whistler‐mode waves in the plasmaspheric plumes (the extension of the plasmasphere at further distances from the Earth), especially the temporal and spatial evolution of plume whistler‐mode waves and associated energetic electron precipitation, requires further investigation. In the present study, by taking advantage of multi‐point measurements, we evaluate the time evolution of whistler‐mode wave driven energetic electron precipitation in both the plumes and the plasma trough regions, with waves observed by RBSP‐B near the equator and electron precipitation detected through enhanced X‐rays observed by BARREL. We show that whistler‐mode waves in both the plumes and the plasma trough account for the energetic electron precipitation, which is essential to understand the radiation belt electron dynamics. Key Points: Modulated energetic electron precipitation is observed by BARREL at L  ∼ 6 from noon to dusk Whistler‐mode waves observed by RBSP‐B are well correlated with electron precipitation both in the plumes and plasma trough Modulation of the modeled electron precipitation driven by whistler‐mode waves is consistent with the enhancement in BARREL X‐rays